Incidence and risk factors of perioperative stroke in siriraj Hospital - Pachara Leemingsawat (2018)
Background: Data concerning perioperative stroke incidence and risk factors are lacking in Thailand. Objective: To study incidence and risk factors ofperioperative stroke in Siriraj Hospital, Bangkok, Thailand. Material and Method: The authors conducted a nested case-control study between July 2007 and June 2010. Consecutive perioperative stroke cases were compared with age-matched controls that had undergone surgery without having a stroke at a 1:4 ratio. Patients'characteristics, co-morbidities, clinical manifestation, stroke subtypes, duration, and types of surgery were collected. Multiple logistic regression analysis was performed to identify factors associated with a stroke during perioperative period. Results: Sixty-six patients with perioperative stroke from 99,283 that underwent surgery were included. This resulted in an incidence of 66.5/100,000. Men comprised 65.2%. Mean age of stroke patients was 66.6-years-old. Age-match controls included 264 consecutive patients who underwent surgery without having a stroke. A multivariate analysis showed that male sex (adjusted OR3.1,p = 0.003), surgical types: open heart surgery (adjusted OR 54.3, p < 0.0001), vascular surgery (adjusted OR 20.6, p < 0.0001) andendovascularprocedure (adjusted OR 15.4, p < 0.0001), emergency surgery (adjusted OR 8.3, p < 0.0001), the presence of diabetes mellitus (adjusted OR 2.6, p = 0.018), chronic kidney disease (adjusted OR 2.6, p = 0.027), and coronary artery disease (adjusted OR 0.4, p = 0.039) were associated with perioperative stroke. Conclusion: Incidence ofperioperative stroke was higher than a previous report. Male, type ofsurgery, emergency operation, diabetes mellitus, and chronic kidney disease were risk factors ofperioperative stroke.